SISTEM PENDUKUNG KEPUTUSAN PEMBERIAN SANKSI PELANGGARAN KEDISIPILAN SISWA PADA SMK PGRI I KEDONDONG - Ipnuwati, Sri (Jurnal Informatika, 2014)
Violation of school rules is often done by the students, among others, the increasingly widespread irregularities norms of religious and social life which is manifested in the form of lack of respect for teachers, less disciplined with time and did not heed the order and regulations of the school, and others. This study builds a decision-making system sanctioning the violation of discipline that has the ability to analyze where each of the criteria in this regard and alternative assessment factors. In this case the students who violate the rules will be sanctioned or point giving priority output intensity value that results in a system that provides an assessment of the student. This decision support system to help make an assessment of each student, to change the criteria and point value changes. It is useful to facilitate decision-making on issues related to discipline. Applications that are created can be used to assist in data processing violations of school discipline, especially the violation of students at SMK PGRI I kedondong the District Kedondong Pesawaran District Lampung Province, and can simplify and accelerate data processing, the student disciplinary violations. With the decision support system is expected to relevant officials would have no difficulty in determining the student who commits an offense (indiscipline) school and for students who violate Rather, they will be sanctioned or point.Keywords: SPK, Violation, Discipline.